(untitled) (Sains Humanika, 2018)
Â The development of computerized technology has transformed teaching and learning scenarios in the classroom. It has become essential learning tool to improve and enhance the quality of teaching and learning process. Thus, the quality of teaching and learning for religious classes Fardhu Ain (KAFA) should be upgraded too through computerised information visualization technology. This research aims to design a computerized information visualization for KAFA class especially for UPKK exams. Then, this courseware will be assessed through perceptions of students and teachers based on four aspects namely the design, ease of use, compatibility of information and satisfaction. This study was combines three methodologies, qualitative, quantitative and product development designs.While the study product development will use ADDIE (Analyze, Design, Development, Implement, Evaluation) approach which is for instructional technology in the production of educational products. The results indicated that students and teachers accept this courseware in the form of its design, ease of use, compatibility of information and satisfaction of use. Hence, advanced studies in context of the development of teaching and learning in KAFA class can still be explored in the future to ensure a better quality of KAFA education.